Carbon dioxide hydrate formation in a three-phase slurry bubble column - Hashemi, Shahrzad (University of Ottawa (Canada), 2009)
Gas hydrates are non-stoichiometric crystalline compounds made of ice-like lattice linked together through hydrogen bonding. Hydrates are being considered as an alternate means of transportation and storage of natural gas as hydrate metastability can be achieved at higher temperature and lower pressure than those required for liquefaction and compression, respectively. Since the mass production of gas hydrates is a developing technology, there is very little data on reactor design and performance available in the open literature. The multiphase reactor of choice is a continuous sparged slurry bubble column which allows relatively high heat and mass transfer rates. The thermodynamics, kinetics and hydrodynamics of this system were studied in this work. In order to predict the solubility of carbon dioxide and methane in water in the presence of hydrate, a model was assembled based on the Trebble-Bishnoi equation of state (1987, Fluid Phase Equil., 35, 1-18), the van der Waals and Platteeuw model (1959, Adv. Chem. Phys., 2, 1-57) and the Holder model (1980, Ind. Eng. Chem. Fund., 19, 282-286). The accuracy of the model was improved by re-adjusting its parameters with recent vapor-liquid water and vapor-liquid water-hydrate equilibrium data of methane-water and carbon dioxide-water systems. In order to estimate the intrinsic kinetic rate constant of hydrate growth, Englezos model (1987, Chem. Eng. Sci., 42, 2647-2658) was reformulated based on a concentration driving force which takes interphase heat transfer into account. The estimation of the intrinsic kinetic rate constant depends on the accuracy of hydrate surface area. The hydrate surface area estimated using a population balance was found to be in good agreement with that based on recently measured data (Bergeron and Servio, 2008, AIChE J, 54 (11), 2964-2970). Gas-liquid interphase mass transfer coefficients were investigated in a three-phase slurry bubble column under CO2 hydrate forming operating conditions. The pressure was varied from 0.1 MPa to 4 MPa while gas velocity was increased up to 0.20 m/s. The effect of temperature was investigated by performing experiment at ambient as well as 277 K. Wettable ion-exchange resin particles were used to simulate the CO2 hydrate. The slurry concentration was varied up to 10 vol.%. Volumetric mass transfer coefficient was found to increase with pressure and superficial gas velocity while it decreased with temperature. No effect of solid was noticed within the range investigated as the rheology of the slurry remained similar to that of water alone. Finally, a reactor model was developed that incorporates the hydrate formation kinetics as well as the system hydrodynamics and interphase mass and heat transfer rates. The model uses a population balance to account for the hydrate growth rate. The mole consumption rate was evaluated as a function of time, temperature, pressure and superficial gas velocity. Moreover, the effect of flow regimes as well as the relative importance of interphase mass transfer and growth kinetics as a function of time and process conditions was discussed.
Keywords: Engineering, Chemical.